anonymous
  • anonymous
What is the value of the y variable in the solution to the following system of equations? 5x + 4y = 1 4x + 3y = -1 A -7 B 7 C 9 D -9
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
I don't know how to do it that's why I need the answers
anonymous
  • anonymous
Please read this: It will be better for you: http://openstudy.com/code-of-conduct
anonymous
  • anonymous
Lame

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
I won't give you answer but I can give you hints on how to solve this.
anonymous
  • anonymous
5x + 4y = 1..................................1 4x + 3y = -1.......................2 From equation 1 5x=1-4y x=1-4y/5 now put into 2nd equ then get value of y . After getting value of y then put into 1st equ to get value of x.
anonymous
  • anonymous
Example: 5x+y=31 [1] x-2y=-7 [2] rearrange [1] to make y the subject. y = 31 - 5x rearrange [2] to make y the subject. -2y = -7 - x 2y = 7 + x y = (7 + x)/2 Now equate your two expressions for y. 31 - 5x = (7+x)/2 2(31 - 5x) = 7 + x 62 - 10x = 7 + x 55 = 11x therefore x = 5 Now sub in x = 5 into [1] or [2] (doesn't matter) [2] -> (5)-2y = -7 -2y = -12 2y = 12 y = 6 So there you have it... x = 5, y = 6. Now follow my approach on your problem
anonymous
  • anonymous
Another approach could be the following: If you multiply the 1st equation by 4 and the second equation by 5, you'll get two equations that both have 20x in them. You can isolate 20X on both and then combine to get a single equation with only Y as the unknown (which is what you're solving for)
anonymous
  • anonymous
do you need help

Looking for something else?

Not the answer you are looking for? Search for more explanations.